2022
DOI: 10.1094/pdis-04-21-0836-re
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting into a Green Winter Cereal Rye Cover Crop on Growth and Development, Seedling Disease, and Yield of Corn

Abstract: Terminating winter cereal rye (Secale cereale L.) cover crops (CCs) 10 or more days before planting corn is recommended to minimize seedling disease and potential yield loss. In Iowa, cold temperatures and frequent precipitation can prevent farmers from following that recommendation and sometimes forcing them to plant corn while the rye plants are still green, referred to as planting green (PG). A field trial was established to evaluate the effect of rye termination shortly before or after corn planting on gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 53 publications
7
33
3
Order By: Relevance
“…Termination timing had a strong effect on the cover crop biomass production in 2019 and 2020 in Ames ( p = 0.0327 and p < 0.0001, respectively; Table 2) and these data concur with other studies done in Iowa (Acharya et al., 2017, 2022). The amount of biomass almost doubled for the later 3 DBP termination compared to the 14 DBP termination.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Termination timing had a strong effect on the cover crop biomass production in 2019 and 2020 in Ames ( p = 0.0327 and p < 0.0001, respectively; Table 2) and these data concur with other studies done in Iowa (Acharya et al., 2017, 2022). The amount of biomass almost doubled for the later 3 DBP termination compared to the 14 DBP termination.…”
Section: Resultssupporting
confidence: 89%
“…According to them, the increased competition between plants in higher populations can reduce individual plant size which can be translated into similar amounts of CR biomass. Termination timing had a strong effect on the cover crop biomass production in 2019 and 2020 in Ames (p = 0.0327 and p < 0.0001, respectively; Table 2) and these data concur with other studies done in Iowa (Acharya et al, 2017(Acharya et al, , 2022. The amount of biomass almost doubled for the later 3 DBP termination compared to the 14 DBP termination.…”
Section: Amessupporting
confidence: 87%
See 2 more Smart Citations
“…Similar corn yield between soil management with a cereal rye cover crop terminated 14 days before planting and cereal rye cover crop terminated at the time of crop planting in this study contradicts research in Iowa which found reduced corn yield when rye termination occurred < 10 days before crop planting (Acharya et al, 2017). Reduced corn grain yield in the late termination treatment at Arlington is supported by research conducted in Maryland, where greater amounts of cereal rye biomass production reduced corn grain yield compared to no cover crop, and Iowa, where termination 12 days after planting reduced corn grain yield (Otte et al, 2019;Acharya et al, 2022). Previous research assessing the long-term impact of using a cereal rye terminated prior to crop establishment has found no reductions in corn yield (Basche et al, 2016;Snapp and Surapur, 2018).…”
Section: Crop Yieldcontrasting
confidence: 50%